Sistema eletrônico para captação de sons respiratórios adventícios em animais submetidos à ventilação mecânica - Valenga, Marcelo Henrique (2009)
This essay presents the project of a portable equipment to capture adventitious respiratory sounds, inside the airways, in animals submitted at mechanical ventilation. It is described the tests for assessment of frequency response and sensitivity of the microphone that was fixed in the tubes of a mechanical ventilator, the behavior of sound propagation in tubes of the system and the characteristics of electronic circuits designed to acquire sound signals by microphones and transferred them to a recording software installed on a personal computer. Tests with the electronic system were performed in three pigs submitted to mechanical ventilation and monitoring in real time the amount of air into the lungs through electrical impedance tomography. Through the recorded sound, it was possible to identify crackles induced in animals by ventilator maneuvers. It was possible to conclude that the developed circuit and setting the microphone in the tube allows to capture crackle sounds on animals with mechanical ventilation, showing a good sound propagation along the airways of the respiratory system. It is also discussed the possibility of using this system with the Electric Impedance Tomography - EIT - to identify the duration and extent of changes in alveolar recruitment during pulmonary ventilation.